The Beliaev-Zelivinsky boson expansion and particle-vibration coupling methods in an exactly soluble model - Bés, Daniel; Evans, J. A.; Kraus, N. C. (1973)
Fil: Bés, Daniel Comisión Nacional de Energía Atómica; Argentina